Proceedings of the 19th International Conference on Intelligent User Interfaces 2014
DOI: 10.1145/2557500.2557521
|View full text |Cite
|
Sign up to set email alerts
|

Teaching motion gestures via recognizer feedback

Abstract: When using motion gestures, 3D movements of a mobile phone, as an input modality, one significant challenge is how to teach end users the movement parameters necessary to successfully issue a command. Is a simple video or image depicting movement of a smartphone sufficient? Or do we need three-dimensional depictions of movement on external screens to train users? In this paper, we explore mechanisms to teach end users motion gestures, examining two factors. The first factor is how to represent motion gestures:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Recent work by Kamal et al [19] explored the effect of using various gesture representation systems, with and without visual feedback, on user performance of motion gestures.…”
Section: Visual Feedback Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Kamal et al [19] explored the effect of using various gesture representation systems, with and without visual feedback, on user performance of motion gestures.…”
Section: Visual Feedback Techniquesmentioning
confidence: 99%
“…The control technique was designed in this way since, at the time this research was conducted, there were no other training techniques for motion gestures that did not additional hardware (such as a Kinect [19]). …”
Section: Design and Proceduresmentioning
confidence: 99%
“…IUI 2017, March 13 -16, 2017, Limassol, Cyprus gestures input from everyday movement [31], teaching appropriate movements necessary to invoke commands [17], and designing reliable recognizers [25].…”
Section: Introductionmentioning
confidence: 99%
“…Related research has shown that delivering appropriate feedback to users during gesture input can help with gesture training [7], increase recognition accuracy [8], and improve overall user experience [5]. However, providing feedback beyond visual and audio cues is still subject of technical development and investigation of user perception of vibrotactile stimuli [1,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…These new devices are worn on various body parts and communicate with the user's smartphone, which is emerging as the central unit of a distributed on-body network of devices [2]. Although prior art has investigated vibrotactile feedback delivered on the smartphone itself [7], no work has examined users' perceptions of feedback decoupled from the smartphone and delivered on the body by an accessory wearable during gesture input with the primary device.…”
Section: Introductionmentioning
confidence: 99%